Screening of Patients for Cochlear Implant Through a Questionnaire Online. GroupProfile of Patients Pre-and Peri lingual Not Summoned - Leal, Aquiles Figueiredo (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Facilitating access to specialized centers and properly screen patients seeking cochlear implants are critical steps for proper rehabilitation.Objective: To describe the group of patients pre-and peri-lingual is not called for in a service evaluation of cochlear implants.Method: A retrospective study analyzed 401 questionnaires of patients pre-and peri-lingual Web site registered in the Central Brazilian cochlear implant. For the failure to call these patients were used as criteria applied some variables: age, use of hearing aids, speech therapy, duration of deafness, type of progression of hearing loss and type of communication used by the patient.Results: The group of patients with pre-and peri-lingual deafness accounted for 34% of total questionnaires completed during the period. The distribution by age found that 54% of patients were over 17 years, 30% between 9 and 17 years, and remaining less than 9 years. The duration of deafness was higher than 20 years in 50% of patients, between 10 and 20 years by 32% between 5 and 10 years in 9% and between 0 and 5 years in 9%. Regarding the performance of voice rehabilitation 58% of patients had performed and 42% did not. Regarding the mode of communication 49% had global communication, 18% LIBRAS, 6% oral communication, 26% no communication.Conclusion: Advanced age, duration of deafness high, so mostly no oral communication and lack of voice rehabilitation were crucial to the failure to call these patients.
Keywords: patient selection; questionnaires; cochlear implant